Rider Revolution (Workshop) / Rosiana Amir ... [et al.] - Amir, Rosiana; Jamal, Zalbahari; Yahya Arif, Noor Ariffah; Shaarin, Wan Mohd Helmi; Dolah, Suhadah (Faculty of Hotel and Tourism Management, 2004)
Revolution Rider is a company owned by 100% "bumiputra". This company plans to give a service in repairing, selling parts and servicing motorcycles. Revolution Rider is a partnership company, which compromises 5 partners.